2023
DOI: 10.1007/s10493-023-00777-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the tomato russet mite provides evidence of oligophagy and a widespread pestiferous haplotype

Abstract: Worldwide, the tomato russet mite (TRM), Aculops lycopersici (Eriophyidae), is a key pest on grown tomatoes besides infesting other cultivated and wild Solanaceae; however, information on TRM basics aspects supporting effective control strategies still lacking, mainly regarding its taxonomic unit and genetic diversity and structure. As A. lycopersici is reported on different species and genera of host plants maybe, populations associated with different host plants constitute specialized cryptic species, such a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…However, our results after analysing partial sequences of the D2 region confirmed a clear separation between D. rubuscolum and other Diptacus species, with genetic variations of 7-25%. Analyses of this region from other Eriophyidae species revealed variation of 2-19% amongst Abacarus species (Duarte et al 2019), 30-36% amongst Aculops species (Duarte et al 2023), 2% between Aceria tosichella Keifer and A. eximia Sukhareva (Skoracka et al 2012), and 4% between Eriocaenus ramosissimi Petanović & Amrine and E. equiseti Farkas (Petanović et al 2015). In all our surveys and despite sampling all plant structures and on six different occasions, we did not find Acalitus essigi or A. orthomera, which have been reported previously on blackberry, R. ulmifolius from Michoacán, Mexico (Ayala-Ortega et al 2019).…”
Section: Discussionmentioning
confidence: 91%
“…However, our results after analysing partial sequences of the D2 region confirmed a clear separation between D. rubuscolum and other Diptacus species, with genetic variations of 7-25%. Analyses of this region from other Eriophyidae species revealed variation of 2-19% amongst Abacarus species (Duarte et al 2019), 30-36% amongst Aculops species (Duarte et al 2023), 2% between Aceria tosichella Keifer and A. eximia Sukhareva (Skoracka et al 2012), and 4% between Eriocaenus ramosissimi Petanović & Amrine and E. equiseti Farkas (Petanović et al 2015). In all our surveys and despite sampling all plant structures and on six different occasions, we did not find Acalitus essigi or A. orthomera, which have been reported previously on blackberry, R. ulmifolius from Michoacán, Mexico (Ayala-Ortega et al 2019).…”
Section: Discussionmentioning
confidence: 91%
“…As well, ribosomal DNA has repeatedly provided insights into the genetic basis of evolution of recently diverged arthropod species and genera, and it is often a good candidate as a molecular taxonomic key for species discrimination [36,37]. For eriophyid species, both the ribosomal ITS and the D1-D12 domains of the 28S region have proven to be informative [20,[38][39][40]. In addition, in the case of candidate ETVs, a diagnostic pipeline using RT-PCR was developed and proved to be effective for the simultaneous identification of eriophyid at the species level and the detection of viruses [41]; in fact, by the incorporation of a reverse transcription step, not only single-copy genomic DNA but also multiple transcripts are targeted, increasing the total amount of template, thus decreasing the minimum number of individuals to be detected; in the meantime, it also allows the amplification of RNA viruses.…”
Section: Discussionmentioning
confidence: 99%
“…TRM is a vagrant eriophyoid mite and, differently from most eriophyoid species, is regarded as a pest in a variety of crops belonging to the Solanaceae family [19]. Presently, TRM can be found in both tropical and temperate parts of the globe with great economic impact, even though the most corroborated hypothesis may lead to a South American origin of TRM [20]. The availability of appropriate diagnostic tests for ToFBV detection is crucial given the growing number of reports and interest in the virus, particularly in light of the rising alert.…”
Section: Introductionmentioning
confidence: 99%
“…However, DNA sequencing of more species, preferably with more than one marker gene is required to elucidate relationships. Studies have shown that when COI is combined with other marker genes such as 28r-RNA, clade structure can change (Duarte et al 2023). This underscores the importance of additional research, integrating barcoding with morphological identification as to make the species delimitation more reliable (Puillandre et al, 2012).…”
Section: Taxonomymentioning
confidence: 99%